Childhood 'bronchitis' and respiratory outcomes in middle-age: a prospective cohort study from age 7 to 53 years. Issue 1 (20th June 2022) - Perret, Jennifer L; Wurzel, Danielle; Walters, E Haydn; Lowe, Adrian J; Lodge, Caroline J; Bui, Dinh S; Erbas, Bircan; Bowatte, Gayan; Russell, Melissa A; Thompson, Bruce R; Gurrin, Lyle; Thomas, Paul S; et al.
Abstract : Background: Chronic bronchitis in childhood is associated with a diagnosis of asthma and/or bronchiectasis a few years later, however, consequences into middle-age are unknown. Objective: To investigate the relationship between childhood bronchitis and respiratory-related health outcomes in middle-age. Design: Cohort study from age 7 to 53 years. Setting: General population of European descent from Tasmania, Australia. Participants: 3202 participants of the age 53-year follow-up (mean age 53, range 51–55) of the Tasmanian Longitudinal Health Study cohort who were born in 1961 and first investigated at age 7 were included in our analysis. Statistical methods: Multivariable linear and logistic regression. The association between parent reported childhood bronchitis up to age 7 and age 53-year lung conditions (n=3202) and lung function (n=2379) were investigated. Results: Among 3202 participants, 47.5% had one or more episodes of childhood bronchitis, classified according to severity based on the number of episodes and duration as: 'non-recurrent bronchitis' (28.1%); 'recurrent non-protracted bronchitis' (18.1%) and 'recurrent-protracted bronchitis' (1.3%). Age 53 prevalence of doctor-diagnosed asthma and pneumonia (p-trend <0.001) and chronic bronchitis (p-trend=0.07) increased in accordance with childhood bronchitis severities. At age 53, 'recurrent-protracted bronchitis' (the most severe subgroup in childhood) was associated with doctor-diagnosed current asthma (OR 4.54, 95% CI 2.31 to 8.91) doctor-diagnosed pneumonia (OR=2.18 (95% CI 1.00 to 4.74)) and, paradoxically, increased transfer factor for carbon monoxide (z-score +0.51 SD (0.15–0.88)), when compared with no childhood bronchitis. Conclusion: In this cohort born in 1961, one or more episodes of childhood bronchitis was a frequent occurrence. 'Recurrent-protracted bronchitis', while uncommon, was especially linked to multiple respiratory outcomes almost five decades later, including asthma, pneumonia and raised lung gas transfer. These findings provide insights into the natural history of childhood 'bronchitis' into middle-age.